Electrostatic Induced Peptide Hydrogels for pH‐Controllable Doxorubicin Release and Antitumor Activity. Issue 36 (21st September 2022) - Tang, Yuanhan; Lu, Yingying; Li, Lingyi; Shi, Changxin; Zhang, Xin; Li, Xinyue; Niu, Yuzhong; Liu, Fangjie; Wang, Linlin; Xu, Wenlong
Abstract: Drug carriers can improve the accuracy of drug efficacy and release behaviors. As drug carrier, short peptide hydrogels have promising future since their good biocompatibility and mechanical properties. In this study, we reported a short peptide (FFWDD) that was used as drug carrier to encapsulate doxorubicin (DOX) hydrochloride by forming a drug‐loaded hydrogel. The prepared hydrogel has complex interlaced network structure and good mechanical strength that allows it to encapsulate the drug. The strong electrostatic interaction between FFWDD and DOX resulted in less release at pH 7.4 and high release at pH 5.5, which may reduce the side effect of DOX. Drug release kinetics showed release in both pH 7.4 and pH 5.5 is in accordance with the Makoid‐Banakar model (R 2 =0.9973 and 0.9964), reflecting the Non‐Fickian diffusion and Quasi‐Fickian diffusion release mechanism by the Korsmeyer‐Peppas model, respectively. CCK‐8 assays demonstrated the excellent biocompatibility of the peptide against human embryonic kidney cells (HEK293) and showed that the antitumor effect of the hydrogel to colon cancer LoVo cells was similar to that of the single DOX. DOX released from the drug delivery system could be taken up by tumor cells in large quantities and accumulate in the nucleus. This research has refined peptide hydrogels as drug carriers, which are expected to be used as drug carriers in biomedical applications. Abstract : A designed peptide loading negative charges was electrostatic combined with the antitumor drug DOX with positive charges. The prepared hydrogel has interlaced network structure and good mechanical strength that allows it to encapsulate the drug. The pH‐responsive hydrogel resulted in less release at pH 7.4 and high release at pH 5.5, which may reduce the side effect of DOX.